The phenomenon of medieval Ius commune: the past of Europe’s legal future? - Lukošius, Tadas (Vilnius University Open Series, 2020)
The historical approach enables us to perceive the specific legal phenomenon as continuous and to study the antecedents of current (or even future) legal challenges. This article discusses the possibilities of invoking the historical notion of ius commune (and various new concepts based on it) in a contemporary legal discourse on the future of the European Union (EU) law. Since issues of integrity and homogeneity remain central to the consideration of further legal developments of the EU legal framework it is especially relevant to look back at one of the most prominent phenomena in the Western legal tradition – ius commune, which to some extent united legal thought throughout pre-modern Europe. By analysing inherent characteristics related to its sources, methods and interaction with other (local) legal systems, we attempt to define the limits of such historical analogy. This may allow answering the questions as to whether and to what extent the model of medieval-originated ius commune could inspire further development of the EU legal framework (as a new ius commune).